Studies on atherosclerosis - Rodriguez-Porcel, Martin; Chade, Alejandro R.; Miller, Jordan D. (Humana Press, 2017)
This volume explores the role free radicals and antioxidants within the development of vascular disease, examining fundamental research and translating preclinical knowledge to clinical trials. The expertly authored chapters describe the relationship of oxidative stress to atherosclerosis and the cardiovascular system, exploring its role in cardiac fibrosis, renovascular disease, hypertension, and regulation of blood pressure and cerebral vascular tone. The concluding chapter discusses the current state of clinical research, contextualizing clinical trials within the existing theoretical framework and analyzing attempts to preserve oxidant stress under various conditions. With its concise and authoritative analysis of pre-clinical research and clinical results, Studies in Atherosclerosis - part of the bestselling Oxidative Stress in Basic Research and Clinical Practice series - is essential for researchers and clinicians focusing in cardiology, nephrology, or oxidative stress.- Resumé vydavatel
Keywords: ateroskleróza; oxidační stres; cytologie; kardiologie; nefrologie; atherosclerosis; oxidative stress; cytology; cardiology; nephrology; elektronické knihy; electronic books